Iron-Catalyzed C–H Bond Activation - Shang, Rui; Ilies, Laurean; Nakamura, Eiichi (Chemical reviews, 2017)
Catalytic C–H bond activation, which was an elusive subject of chemical research until the 1990s, has now become a standard synthetic method for the formation of new C–C and C–heteroatom bonds. The synthetic potential of C–H activation was first described for ruthenium catalysis and is now widely exploited by the use of various precious metals. Driven by the increasing interest in chemical utilization of ubiquitous metals that are abundant and nontoxic, iron catalysis has become a rapidly growing area of research, and iron-catalyzed C–H activation has been most actively explored in recent years. In this review, we summarize the development of stoichiometric C–H activation, which has a long history, and catalytic C–H functionalization, which emerged about 10 years ago. We focus in this review on reactions that take place via reactive organoiron intermediates, and we excluded those that use iron as a Lewis acid or radical initiator. The contents of this review are categorized by the type of C–H bond cleaved and the type of bond formed thereafter, and it covers the reactions of simple substrates and substrates possessing a directing group that anchors the catalyst to the substrate, providing an overview of iron-mediated and iron-catalyzed C–H activation reported in the literature by October 2016.